Respuestas

  • Usuario de Brainly
2013-03-12T17:25:41+01:00

(-4-i+3+i^63).................(-2-i)

---------------------- = ----------------

...........z............................(1-i)

 

aplicamos la propiedad fundamental de proporciones

 

(-4-i+3+i^63)(1 - i) = (-2-i). z

( -1 - i +i^63)(1 -i) = (-2 - i) . z...................i^63 = i³ = - i

(- 1 - i - i )(1 -i) = (-2-i) .z

(-1 - 2i)(1-i) = (-2-i).z

-1 +i - 2i + 2i² = (-2 - i) . z

-1 - i + (-2) = (-2 -i) . z

- 3 - i

------------ = z

( - 2- i )

 

(- 3 - i)(-2-i)

------------------- = z

( - 2- i ) (-2-i)

 

6 + 3i +2i + i²

--------------------- = z

4 - i²

 

5 + 5i

------------ = z

4 -(-1)

 

5 + 5i

------------ = z

....5

 

 

1 + i = z

 

 

espero que te sirva, salu2!!!!